PENGARUH MOTIVASI TERHADAP DISIPLIN DAN KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KOTA DENPASAR - Ni Made Raka Kumarawati; Gede Suparta; Putu Ngurah Suyatna Yasa (Universitas Warmadewa, 2017)
Given the importance of discipline and employee performance, the issue which is of particular interest are the factors that incluence it, among others, motivation. Otherwise in Sekretariat Daerah Kota Denpasar an effort to get employess who have the discipline and high performance, have noticed work motivation. The formulation of the problem in this research is whether motivation influence on discipline, whether motivation influence on employee performance, whether discipline influence on empoloyee performance and how function of discipline in mediation influence motivation on employee performance, and to answer the problem, we conducted research with used sample 69 respondence. Data collected by questionnaire. The analysis technique used is Parsial Least Square (PLS) Version 20. Based on the results obtained conclusions include: motivation have positive influence and not significant to discipline at Sekretariat Daerah Kota Denpasar, motivation have positive influence and significant to employee performance at Sekretariat Daerah Kota Denpasar. Discipline have negative influence and not significant influence to employee performance at Sekretariat Daerah Kota Denpasar. Discipline is not mediation between motivation to employee performance at Sekretariat Daerah Kota Denpasar.